My big fat Greek wedding 2 - Jones, Kirk, 1964-; Vardalos, Nia, 1962-; Corbett, John, 1961-; Constantine, Michael; Lennertz, Christopher (Universal City, CA : Universal Pictures Home Entertainment, 2016)
While Toula and Ian struggle to deal with their seventeen-year-old daughter, they uncover a secret that leads to another family wedding.
Originally released as a motion picture in 2016.
Sequel to the film "My big fat Greek wedding" (2002).
Dolby digital 5.1, anamorphic wide screen 2.40:1.
Features: gag reel, Making the Greekquel, My big fat Greek dinner.
Cinematographer, Jim Denault ; production design, Gregory P. Keen ; editor, Markus Czyzewski ; music, Christopher Lennertz.
Nia Vardalos, John Corbett, Michael Constantine, Lainie Kazan, Andrea Martin.
Keywords: Greek Americans -- Drama; Families -- Drama; Weddings -- Drama; Mothers and daughters -- Drama; Teenagers -- Drama; Romantic comedy films; Romance films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Comedy films